ANALISIS PENGGUNAAN KONFIKS PADA KARANGAN TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 2 PEDAN - Any Novitasari; Yakub Nasucha (Literasi : Jurnal Bahasa dan Sastra Indonesia serta Pembelajarannya, 2021)
This study aims to 1) describe the use of confixes in descriptive texts for seventh grade students of SMP Negeri 2 Pedan and 2) describe the meaning of using confixes in descriptive texts for seventh grade students of SMP Negeri 2 Pedan. The type of research used is qualitative by using descriptive methods in describing the data found. The data in this study are the use of confixes in descriptive text essays, while the source of data in this study is descriptive text essays for seventh grade students of SMP Negeri 2 Pedan. The data collection technique used is listen and note. Test the validity of the data using the document triangulation technique. Data analysis carried out in this study is an interactive analysis model. The result of this research is that the use of confix found in this study has six kinds of forms of conflict, namely ke-an, pe-an, role, ber-an, se-nya, and se-an. The researcher found 48 data from 32 student essays in the form of the use of confixes. The use of confixes includes 22-word confixes, 11-word verb confixes, 5-word role-playing confixes, 5-word confixes, 4-word se-an confixes, and 1-word confixes. said. The use of confixes can be formed through four basic elements, including adjectives, verbs, nouns, and adverbs. The meanings contained in the data are 26, including 9 meanings of the confix, 7 meanings, 4 role confixes, 3 meanings, 3 meanings, 2 meanings, and confix se-an as much as 1 meaning.